Inflammasome Activity in Response to Influenza Vaccination Is Maintained in Monocyte-Derived Peripheral Blood Macrophages in Older Adults - Crooke, Stephen N.; Goergen, Krista M.; Ovsyannikova, Inna G.; Kennedy, Richard B. (Frontiers in Aging, 2021)
Introduction: Each year, seasonal influenza A results in a large number of hospitalizations (90%) and deaths (70%) among adults who are >65 years old. Inflammasome activation has been shown to be important for protection against influenza infection in animal models but has not yet been demonstrated in humans. We hypothesized that age-related dysfunction (immunosenescence) of the inflammasome may be associated with poor influenza-vaccine response among older adults. Methods: A cohort of younger (18–40 years of age) and older (> 65 years of age) adults was recruited prior to the 2014–2015 influenza season. We measured hemagglutination inhibition (HAI) titers in serum before and 28 days after receipt of the seasonal inactivated influenza vaccine. Inflammasome-related gene expression and protein secretion were quantified in monocyte-derived macrophages following stimulation with influenza A/H1N1 virus. Results: Younger adults exhibited higher HAI titers compared to older adults following vaccination, although inflammasome-related protein secretion in response to influenza stimulation was similar between the age groups. Expression of P2RX7 following influenza stimulation was lower among older adults. Interestingly, CFLAR expression was significantly higher among females (p=2.42x10-5) following influenza stimulation and this gene may play an important role in the development of higher HAI antibody titers among older females Conclusion: Inflammasome activation in response to influenza vaccination appears to be maintained in monocyte-derived macrophages from older adults and does not explain the poor influenza vaccine responses generally observed among this age group.